2013
DOI: 10.1161/circimaging.113.000389
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letter Regarding Article, “Cardiac Magnetic Resonance Imaging: A New Gold Standard for Ventricular Volume Quantification During High-Intensity Exercise”

Abstract: We thank Drs Yoneyama and Akashi for their important reference to the confounding influence of respiration on biventricular volume assessment by real-time cardiac magnetic resonance imaging. As we noted in the Discussion, changes in biventricular volumes "may be caused by physiological differences in preload attributable to the fall in intrathoracic pressures during inspiration and cardiac translation through the imaging plane."1 Real-time cardiac magnetic resonance imaging provides a novel means of expanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
165
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 86 publications
(170 citation statements)
references
References 3 publications
3
165
0
2
Order By: Relevance
“…However, our group and others have shown significant stroke volume increase also during supine exercise by using cardiac magnetic resonance imaging (23,36), and a comparative study in children between upright and supine CPET has additionally found good correlation of parameters (29).…”
Section: Methodology Limitationsmentioning
confidence: 55%
“…However, our group and others have shown significant stroke volume increase also during supine exercise by using cardiac magnetic resonance imaging (23,36), and a comparative study in children between upright and supine CPET has additionally found good correlation of parameters (29).…”
Section: Methodology Limitationsmentioning
confidence: 55%
“…11 Using this novel CMR methodology with simultaneous invasive vascular pressure recordings during exercise, we evaluated exercise hemodynamics and the effect of sildenafil on exercise hemodynamics in Fontan patients. We hypothesized that (1) the exercise capacity in patients with a Fontan circulation and seemingly normal anastomotic and ventricular function is limited attributable to an impaired augmentation in pulmonary vascular flow, and (2) sildenafil would improve pulmonary vascular flow and ventricular preload during exercise.…”
Section: Circ Cardiovasc Imagingmentioning
confidence: 99%
“…24 Although CI nearly doubled during exercise in this study, peak CI was still lower than would be expected in healthy young individuals. 11 First, as measures reflecting preload, changes in EDVi and TPRi were evaluated. In a normal circulation, preload is determined by upstream factors such as venous return as well as right ventricular, pulmonary vascular, and atrial function.…”
Section: Determinants Of Exercise Limitation In Fontan Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed a methodology which combines invasive PAP measures with gold-standard cardiac magnetic resonance (CMR) quantification of RV function and Q during exercise and have used this technique to identify sub-clinical pulmonary vascular dysfunction and RV dysfunction (9,10). Thus, this technique is ideally suited to assess our hypothesis that abnormal pulmonary vascular and RV function would be demonstrable during exercise in asymptomatic subjects with a known BMPR2 mutation.…”
Section: Introductionmentioning
confidence: 99%